2019
DOI: 10.35588/blacpma.19.18.1.06
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric studies of Sideritis scardica Grsb. and S. syriaca L. in their natural populations in Bulgaria

Abstract: Morphometric studies of Sideritis scardica Grsb. and S. syriaca L. in their natural populations in Bulgaria [Estudios morfométricos de Sideritis scardica Grsb. y S. syriaca L. en sus poblaciones naturales en Bulgaria]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…The phenotypic evaluation of S. scardica's populations from the six case study sites revealed a high morphological diversity of leaf and inflorescence traits, as observed from the coefficient of variations (higher than 15%). Similar to our data, Aneva and Zhelev (2019) [62] reported high phenotypic diversity (coefficient of variation (CV) higher than 20%) among six wild populations of S. scardica in Bulgaria. Several studies report the phytochemical profiling and bioactivities of Sideritis sp.…”
Section: Discussionsupporting
confidence: 90%
“…The phenotypic evaluation of S. scardica's populations from the six case study sites revealed a high morphological diversity of leaf and inflorescence traits, as observed from the coefficient of variations (higher than 15%). Similar to our data, Aneva and Zhelev (2019) [62] reported high phenotypic diversity (coefficient of variation (CV) higher than 20%) among six wild populations of S. scardica in Bulgaria. Several studies report the phytochemical profiling and bioactivities of Sideritis sp.…”
Section: Discussionsupporting
confidence: 90%
“…The applied cluster and principal component analyses clearly separated the population Chervenata Stena from the remaining populations of both S. scardica and S. syriaca (see [15]). The applied cluster and principal component analyses clearly separated the population Chervenata Stena from the remaining populations of both S. scardica and S. syriaca (see [15]).…”
Section: Morphological and Morphometric Datamentioning
confidence: 93%
“…The applied cluster and principal component analyses clearly separated the population Chervenata Stena from the remaining populations of both S. scardica and S. syriaca (see [15]). The applied cluster and principal component analyses clearly separated the population Chervenata Stena from the remaining populations of both S. scardica and S. syriaca (see [15]). The juvenile seedlings of S. scardica from Trigrad and S. elica differed clearly in their pubescence although both localities are situated in the same mountain range (Figure 4).…”
Section: Morphological and Morphometric Datamentioning
confidence: 93%
See 1 more Smart Citation
“…Therefore, studying of individuals from natural populations could be more sound. Unfortunately, this is not always possible when making the taxonomic revisions and in most cases the researcher relies on incomplete set of herbarium specimens (Aneva & Zhelev, 2019).…”
Section: Introductionmentioning
confidence: 99%